Zapuščena naselja v gorskih območjih Furlanije - Julijske krajine - Jelen, Igor (Geografski vestnik, 2022)
The aim of this work is to demonstrate that new immigrations improve the appearance and socioeconomic situation of remote alpine regions. Friuli mountain villages, having become sparsely inhabited or indeed real ghost towns, are particularly suitable areas for such studies. The research builds on the one hand on analysis of the current state of the art as well as on analyses of official statistical data. It is on the other hand derived from own surveys in the course of investigative visits to all ghost towns in the research area. The results show that newcomers bring innovation and new impulses in agriculture, tourism, artistic and cultural sphere and play a key role in renovating existing buildings, reusing fallow plots of land and establishing a creative dynamic. Their activities increasingly enable the regeneration and maintenance of alpine cultural landscapes, resulting in new social and agrarian structures, which are emerging as »new farming« in the study area. The village of Dordolla in the Aupa Valley has recently established itself as a centre of innovation of these new processes and its achievements are evident in the rest of the valley, too. The regeneration processes analysed in the study area could also be transferred to other remaining partially abandoned settlements in Friuli-Venezia Giulia and broader.
Keywords: demografija; Friuli-Venezia Giulia; Furlanija - Julijska krajina; ghost villages; gorska območja; Italija; Italy; migracije; migration; mountains; odseljevanje; revitalizacija; revitalization planning; vasi